The joint association of physical activity and sedentary behavior with metabolic syndrome among urban men aged 60+ years in regional China - Lou, Qinglin; Wu, Haidi; Li, Guang; Hu, Yan; Ye, Qing; Gu, Shouyong; Xu, Fei (Frontiers in Public Health, 2022)
Objectives Metabolic syndrome (MetS) is a major public health issue worldwide, which is preventable through physical activity (PA) promotion and sedentary behavior (SB) reduction. However, the joint association of PA and SB with MetS was not well-investigated, particularly in elderly people. This study aimed to examine separate and joint associations of PA and SB with MetS among elderly urban men in China. Methods In this cross-sectional study conducted in mid-2018, participants were urban men aged 60+ years randomly selected from in Nanjing of China. Exposure variables were PA and SB. The outcome variable was MetS. A participant was categorized as “having MetS” or “not having MetS” in the analysis. Independent variables were PA and SB, which were categorized as “sufficient PA or insufficient PA” and “shortened SB or prolonged SB”, respectively. Mixed-effects logistics regression models were applied to calculate odds ratios (ORs) and 95% confidence intervals (CIs) to assess the association of PA and SB with MetS. Results Totally, 5,520 from 5,792 eligible participants were randomly recruited and their mean age was 68.9 (standard deviation: 16.9) years. The prevalence of MetS was 30.8% (95%CI = 29.6%, 32.0%) among urban men aged 60+ years in the study. After adjustment for potential confounders, subjects with sufficient PA were less likely (OR = 0.77, 95%CI = 0.67, 0.88) to experience MetS, independently of SB, relative to their counterparts with insufficient PA, while a lower odds (OR = 0.74; 95%CI = 0.61, 0.89) of experiencing MetS was examined for participants with shortened SB, also independently of PA, compared to those with prolonged SB in the study. Furthermore, compared to participants with insufficient PA and prolonged SB, those either within categories of insufficient PA and shortened SB (OR = 0.81; 95%CI = 0.65, 0.99), sufficient PA and prolonged SB (OR = 0.80; 95%CI = 0.70, 0.92), or sufficient PA and shortened SB (OR = 0.41; 95%CI = 0.26, 0.63) were at significantly lower risk to experience MetS, respectively. Conclusions PA was negatively associated with MetS, and SB was positively linked to MetS, which were independent of each other. Moreover, sufficient PA and shortened SB might exert additively joint influence on MetS. This study has important implications that concurrent PA promotion and SB reduction shall be encouraged for people to optimize the effectiveness of MetS prevention.